Development and ex-vivo skin permeation studies of finasteride–poly(lactic acid-co-glycolic acid) and minoxidil–chitosan nanoparticulate systems. (March 2020) - Pervaiz, Fahad; Saleem, Madiha; Ashames, Akram; Rehmani, Sahrish; Qaiser, Rubina; Noreen, Sobia; Murtaza, Ghulam
This study was designed to improve the permeability of two drugs (finasteride and minoxidil) through the skin. Finasteride-loaded poly(lactic acid- co -glycolic acid) and minoxidil-loaded chitosan nanoparticles were prepared by nanoprecipitation and ionic gelation method, respectively, and subsequently incorporated into semisolid Carbopol 940 gel. These fabricated nanoparticles were characterized for their pharmaceutical and chemical behavior. Nanoparticles were found a nearly spherical shape in the scanning electron microscopic studies and exhibited particle size in a range of 211–1012 nm. Finasteride- and minoxidil-loaded nanoparticles were optimized for relatively higher entrapment efficiency of 98% and 95%, respectively, by using the optimal concentration of polymers and stabilizers. All formulations were clear with smooth homogeneous texture and having pH values compatible with that of skin. This nanoparticulate system suspended in gel prolonged the release of drugs for up to 24 h and enhanced the drug permeability through the skin and retention of drug-loaded nanoparticles within the hair follicular routes. Therefore, these nanoparticles incorporated in the gel were found as a promising candidate for topical application in the treatment of alopecia by reducing the dosing frequency and adverse effects and as an effective strategy for improving the patient compliance toward therapy.